The Function of -teʔ in Chepang - Caughley, Ross C. (Nepalese Linguistics, 2024)
There has been considerable discussion in the past concerning the function of an unusual morpheme -teʔ that occurs in Chepang and its relationship to a proposed Proto-Tibeto-Burman 2nd person prefix #ta1. Its unusualness comes from its distribution and function in Chepang clauses. This paper discusses the full extent of the distribution and function of -teʔ, also the question as to whether it can be regarded as a 2nd person marker in Chepang and a suggestion as to how it may have originated for this language. This study is based on the West Makwanpur variety of Chepang, where the morpheme has some of its most distinctive features